Convergência de saberes: a integração dos conhecimentos científicos e populares no campo da Agroecologia - Silva, Anna Carolina Santana da (Universidade Federal de São Carlos, 2018)
The construction of scientific knowledge is one of the objects that the social studies of Science, Technology and Society propose to investigate. This area of ​​study discusses the importance of placing scientific knowledge on an equal footing with other forms of knowledge, especially considering that science is also permeated with values ​​of social and ethical order. From the contact with practical experiences, also described in the scientific literature, it is known that rural extension organizations, working from the perspective of Agroecology - ecological food production field - have in their assumptions the valorization of traditional knowledge and usually adopt methodological practices that promote the integration of different knowledge. The aim of this project was to analyze the experiences of two organizations that work with agroecological rural extension in order to understand if their theoretical and methodological bases are consistent with the search for the horizontal construction of scientific / academic knowledge and popular / traditional knowledge. The methodology used was documentary analysis, using a qualitative approach, in which documents were selected and analyzed to enable the collection of information about the organizations, their theoretical bases and methodological practices. The results showed that the studied organizations use theoretical references of Agroecology, in addition to other authors that discuss the collective construction of knowledge. Regarding methodological practices adopted by the organizations, the data showed that both use participatory tools in their practices, such as Participatory Rural Diagnosis, Participatory Action Research, group work, field days, among others. It is concluded, then, that the theoretical and methodological bases of organizations working with Agroecology presuppose the convergence between scientific and popular knowledge and that, although there are still obstacles and difficulties in the implementation of actions by these organizations, these are practical examples of that it is possible to construct scientific knowledge that considers and respects traditional / popular knowledge.
Convergence of knowledges: the integration of scientific and popular knowledge in the field of Agroecology
Keywords: Extensão rural; Construção de conhecimentos; Conhecimento popular; Agroecologia; Conhecimento científico; Rural extension; Knowledge construction; Popular knowledge; Agroecology; Scientific knowledge; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS; CIENCIAS SOCIAIS APLICADAS